Serogroup C Neisseria meningitidis disease epidemiology, seroprevalence, vaccine effectiveness and waning immunity, England, 1998/99 to 2015/16 - Findlow, Helen (Euro Surveill, 2019)
BACKGROUND: In 1999, the United Kingdom (UK) was the first country to introduce meningococcal group C (MenC) conjugate vaccination. This vaccination programme has evolved with further understanding, new vaccines and changing disease epidemiology. AIM: To characterise MenC disease and population protection against MenC disease in England. METHODS: Between 1998/99–2015/16, surveillance data from England for laboratory-confirmed MenC cases were collated; using the screening method, we updated vaccine effectiveness (VE) estimates. Typing data and genomes were obtained from the Meningitis Research Foundation Meningococcus Genome Library and PubMLST Neisseria database. Phylogenetic network analysis of MenC cc11 isolates was undertaken. We compared bactericidal antibody assay results using anonymised sera from 2014 to similar data from 1996–1999, 2000–2004 and 2009. RESULTS: MenC cases fell from 883 in 1998/99 (1.81/100,000 population) to 42 cases (0.08/100,000 population) in 2015/16. Lower VE over time since vaccination was observed after infant immunisation (p = 0.009) and a single dose at 1–4 years (p = 0.03). After vaccination at 5–18 years, high VE was sustained for ≥ 8 years; 95.0% (95% CI: 76.0– 99.5%). Only 25% (75/299) children aged 1–14 years were seroprotected against MenC disease in 2014. Recent case isolates mostly represented two cc11 strains. CONCLUSION: High quality surveillance has furthered understanding of MenC vaccines and improved schedules, maximising population benefit. The UK programme provides high direct and indirect protection despite low levels of seroprotection in some age groups. High-resolution characterisation supports ongoing surveillance of distinct MenC cc11 lineages.